State and Business Groups in the Space Industry - Yunita Permatasari (Andalas Journal of International Studies (AJIS), 2018)
Space exploration is growing from cold war to present. Actors also began to change, not only developed state or developing state, but also industry. Industry offers more economical space exploration, which is driving the industry increasing. However, state remains primary party responsible for ensuring space exploration are peaceful purposes and beneficial to all mankind. Thus, need to analyze how state and business groups relationships in the development of the private space industry? The method to be used in this research is content analysis related to governed interdependence. The analysis will use source data in the form of journals, books, and media information about the development of space industry by the state and business groups that influence it in political economy. From the analysis results know that the pattern of relationship between countries and groups in the development of space industry is interdependence to develop a world class strategic industry. This paper is important in the development of international political economy concept.